Assesment of Endometrial Vascularization with Immunohistochemical CD34 Assay in Recurrent Pregnancy Loss: A Case Control Study - Aydın, Emine; Usta, Taner (Gynecology Obstetrics & Reproductive Medicine, 2017)
Objectives: We compared the endometrial vascularization in hysteroscopic endometrial samplings between recurrent pregnancy loss (RPL) and control group. Study Design: We prospectively evaluated hysteroscopic endometrial samplings from RPL and control groups. CD34 transmembrane protein was used for evaluating endometrial vascularization. The vascularization was assessed based on thickness of vessels, diameter of the largest vessel, and number of vessels per mm2 in CD34-stained slides. Results: There was no significant difference in demographic findings and vascularization, such as largest vessel diameter (p: 0.572), and number of vessels per mm2 (p: 0.982) between the two groups. Conclusion: The cycling endometrium is a highly angiogenic tissue and may play a role in the etiology of RPL. However, we find a weak relationship between endometrial vascularization and RPL.